Role of Growth Arrest–Specific Gene 6 in the Development of Fungal Allergic Airway Disease in Mice - Shibata, Takehiko; Ismailoglu, Ugur Burcin; Kittan, Nicolai A.; Moreira, Ana Paula; Coelho, Ana Lucia; Chupp, Geoffrey L.; Kunkel, Steven L.; Lukacs, Nicholas W.; Hogaboam, Cory M. (American journal of respiratory cell and molecular biology, 2014)
Growth arrest-specific gene (Gas)6 is a secreted vitamin K-dependent protein with pleiotropic effects via activation of receptor tyrosine kinase Tyro3, Axl, and Mertk receptors, but little is known about its role in allergic airway disease. We investigated the role of Gas6 in the development of fungal allergic airway disease in mice. The immune response was evaluated in Gas6-deficient (Gas6-/-) and wild-type (WT) mice and in recombinant Gas6-treated WT mice during Aspergillus fumigatus-induced allergic airway disease. Gas6 plasma levels were significantly elevated in adult clinical asthma of all severities compared with subjects without asthma. In a murine model of fungal allergic airway disease, increased protein expression of Axl and Mertk were observed in the lung. Airway hyperresponsiveness (AHR), whole lung Th2 cytokine levels, goblet cell metaplasia, and peribronchial fibrosis were ameliorated in Gas6-/- mice compared with WT mice with fungal allergic airway disease. Intranasal Gas6 administration into WT mice had a divergent effect on airway inflammation and AHR. Specifically, a total dose of 2 μg of exogenous Gas6 (i.e., low dose) significantly increased whole lung Th2 cytokine levels and subsequent AHR, whereas a total dose of 7 μg of exogenous Gas6 (i.e., high dose) significantly suppressed Th1 and Th2 cytokines and AHR compared with appropriate control groups. Mechanistically, Gas6 promoted Th2 activation via its highest affinity receptor Axl expressed by myeloid DCs. Intranasal administration of Gas6 consistently exacerbated airway remodeling compared with control WT groups. These results demonstrate that Gas6 enhances several features of fungal allergic airway disease.